2017
DOI: 10.1155/2017/1703608
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Location Routing Problem considering Uncertain Data after Disasters

Abstract: The relief distributions after large disasters play an important role for rescue works. After disasters there is a high degree of uncertainty, such as the demands of disaster points and the damage of paths. The demands of affected points and the velocities between two points on the paths are uncertain in this article, and the robust optimization method is applied to deal with the uncertain parameters. This paper proposes a nonlinear location routing problem with half-time windows and with three objectives. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…It is shown that most of the recently proposed LRP models are still considering only deterministic data (76.58%). However, SLRP (e.g., Bertazzi and Maggioni, 2017;Chang et al, 2017;Saragih et al, 2019) and FLRP (e.g. Ghezavati and Morakabatchian, 2015;Zhalechian et al, 2016;Pekel and Kara, 2019) have started to receive more recognition with the presence of 5.86% and 15.32% from the total publications.…”
Section: Scenario Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that most of the recently proposed LRP models are still considering only deterministic data (76.58%). However, SLRP (e.g., Bertazzi and Maggioni, 2017;Chang et al, 2017;Saragih et al, 2019) and FLRP (e.g. Ghezavati and Morakabatchian, 2015;Zhalechian et al, 2016;Pekel and Kara, 2019) have started to receive more recognition with the presence of 5.86% and 15.32% from the total publications.…”
Section: Scenario Characteristicsmentioning
confidence: 99%
“…Only five articles have addressed the plan (Bertazzi and Maggioni, 2015;Tokgöz et al, 2015;Farrokhi-Asl et al, 2017;Tokgöz and Trafalis, 2017;Ghaffarinasab et al, 2018), while one work deals with the case where facilities can be positioned in any vertex and arc of a graph (Averbakh and Yu, 2018). The LARP also receives a little attention, with only 10 works (4.52%) found within the considered timeframe (Lopes et al, 2014;Riquelme-Rodríguez et al, 2016;Chang et al, 2017;Boccia et al, 2018;Çetinkaya et al, 2018;Chen et al, 2018;Cui et al, 2018;Amini et al, 2019;Fernández et al, 2019;Lu et al, 2019a).…”
Section: Physical Characteristicsmentioning
confidence: 99%
“…Chang et al [22] studied the impact of large disasters on roads safety and suggested for this reason a nonlinear site distribution for vehicle routing problem on the affected points.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because emergency supplies tend to be infrequently used, intelligent storage systems are seldom used for emergency supplies, and therefore, there has been little research on storage location allocation in intelligent emergency logistics [32][33][34][35][36]. The emergency supply reserve warehouses of some power agencies have used the Internet of Things to construct intelligent storage systems for their emergency power supplies [37], which has enabled substantial increases in storage automation and storage and retrieval performance, reduced injuries and supply losses, and enhanced the emergency response capabilities.…”
Section: Introductionmentioning
confidence: 99%